TRANSFORMASI AKUAKULTUR MELALUI REKAYASA GENETIK DAN BIOTEKNOLOGI: IMPLIKASI TERHADAP PRODUKSI DAN KUALITAS IKAN - Rita Hayati; Maheran Mulyadi (CV. Adiba Aisha Amira, 2026)
The rapid growth of the aquaculture sector, the leading provider of global animal protein, demands the application of technological innovations that sustainably improve the productivity, health, and quality of farmed fish. Genetic engineering and biotechnology have become strategic tools for transforming modern aquaculture systems by improving fish genetic traits, increasing disease resistance, and optimizing product quality. This study aims to conduct a comprehensive literature review of the role of genetic engineering and biotechnology in aquaculture transformation, focusing on its implications for the production, health, and quality of farmed fish. The research method is a qualitative approach based on library research, analyzing reputable scientific articles indexed in the Scopus, Web of Science, and Google Scholar databases. The analysis used thematic content analysis to identify patterns, conceptual frameworks, research trends, and key research gaps. The study found that marker-assisted genetic selection, genomics, and CRISPR-Cas9-based gene editing significantly improved growth rate, feed efficiency, and disease resistance in fish. In addition, the development of biotechnology-based recombinant vaccines, probiotics, and biosensors contributes to improving fish health, food safety, and the quality of aquaculture products. However, the study also identified a range of challenges, including ecological risks, biosecurity issues, regulation, and social acceptance of genetically engineered organisms. Therefore, the transformation of biotechnology-based aquaculture needs to be balanced with a strong policy framework, a prudential approach, and sustainable governance. This research is expected to make a theoretical contribution to the development of modern aquaculture science and to have practical implications for the formulation of innovative, inclusive, and environmentally friendly fisheries industry strategies.